Hepatic Vein Balloon Occlusion to Mitigate the Heat Sink Effect during Percutaneous Liver Ablation - Braaten, Tyler; Tran Cao, Hop S.; Huang, Steven Y. (Digestive Disease Interventions, 2021)
Hepatocellular carcinoma (HCC) commonly affects patients with cirrhosis. Patients with early-stage disease may be treated with surgery, liver transplantation, and locoregional therapy (e.g., thermal ablation and chemoembolization). The treatment efficacy of thermal ablation can be limited by factors such as proximity to adjacent vessels, which may create a heat sink effect. The heat sink effect can be mitigated by intravascular balloon occlusion. Our case report demonstrates the utility of balloon occlusion during thermal ablation of HCC adjacent to the right hepatic vein complicated by hepatic vein thrombosis.
Keywords: hepatic vein balloon occlusion; hepatic vein thrombosis; ablation